Claudin-7 promotes the epithelial: mesenchymal transition in human colorectal cancer - Philip, Rahel; Heiler, Sarah; Mu, Wei; Büchler, Markus W.; Zöller, Margot; Thuma, Florian (OncoTarget, 2015)
In colorectal cancer (CoCa) EpCAM is frequently associated with claudin-7. There is evidence that tumor-promoting EpCAM activities are modulated by the association with claudin-7. To support this hypothesis, claudin-7 was knocked-down (kd) in HT29 and SW948 cells., HT29-cld7kd and SW948-cld7kd cells display decreased anchorage-independent growth and the capacity for holoclone-, respectively, sphere-formation is reduced. Tumor growth is delayed and cld7kd cells poorly metastasize. In line with this, migratory and invasive potential of cld7kd clones is strongly impaired, migration being inhibited by anti-CD49c, but not anti-EpCAM, although motility is reduced in EpCAM siRNA-treated cells. This is due to claudin-7 recruiting EpCAM in glycolipid-enriched membrane fractions towards claudin-7-associated TACE and presenilin2, which cleave EpCAM. The cleaved intracellular domain, EpIC, promotes epithelial-mesenchymal transition (EMT)-associated transcription factor expression, which together with fibronectin and vimentin are reduced in claudin-7kd cells. But, uptake of HT29wt and SW948wt exosomes by the claudin-7kd lines sufficed for transcription factor upregulation and for restoring motility., Thus, claudin-7 contributes to motility and invasion and is required for recruiting EpCAM towards TACE/presenilin2. EpIC generation further supports motility by promoting a shift towards EMT. Notably, EMT features of cld7-competent metastatic CoCa cells can be transferred via exosomes to poorly metastatic cells.